Do Sustainability Practices Create Value? Evidence from Green Banking, Islamic Social Reporting, and Profitability in Indonesian Islamic Banks - Fathihani Fathihani; Putri Dwi Wahyuni; Maria Lusiana Yulianti; Yuni Shara; Fatlina Zainuddin (Shirkah: Journal of Economics and Business, 2026)
Despite the increasing adoption of sustainable finance practices, the combined effects of green banking and Islamic Social Reporting (ISR) on firm value, particularly through financial performance, remain underexplored. This study aims to examine the effects of green banking and ISR on firm value in Indonesian Islamic banks, as well as the moderating role of profitability. Employing a quantitative explanatory design, the study utilizes secondary data obtained from annual reports and sustainability reports of 14 Islamic commercial banks in Indonesia during the period 2020–2024. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA) with EViews. The findings reveal that green banking and ISR have positive and significant effects on firm value, indicating that environmental sustainability initiatives and Sharia-based social accountability enhance market valuation and stakeholder trust. Profitability is also found to positively influence firm value and significantly strengthens the effects of green banking and ISR on firm value. Furthermore, firm size and leverage contribute to explaining variations in firm value. These findings suggest that sustainability practices generate greater organizational value when supported by strong financial performance. The study contributes to the sustainable finance and Islamic banking literature by demonstrating the complementary roles of environmental responsibility, social accountability, and profitability in creating long-term firm value.